Agreement Between Caregivers' Concerns of Children's Developmental Problems and Professional Identification in Taiwan - Lin, Ling-Yi; Yu, Wen-Hao; Lin, Wei-Pin; Chen, Chih-Chia; Tu, Yi-Fang (Frontiers in Pediatrics, 2022)
Objective Early detection of developmental delays relies on the accuracy of the caregivers' concerns of children's developmental problems. The aim of this study was to investigate the agreement between the caregivers' awareness of children's developmental problems and professional identification. Methods Caregivers of 1,963 children (age range: 5–71 months; mean: 38.4 months) younger than 6 years old who were at risk of developmental delays and referred to the center for a comprehensive evaluation were enrolled in this study. Children were identified by a transdisciplinary team including a pediatric neurologist, a pediatric psychiatrist, two psychologists, two occupational therapists, two physical therapists, two speech therapists, a social worker, and a special instructor. A series of standardized developmental assessments were used to identify children with developmental delay. Retrospective chart reviews were conducted on all children to confirm specific developmental disorders. Results The caregivers' initial concerns of cognitive, speech/language, emotional/behavioral, and motor and global development showed low agreement with the results of professional identification. The major disagreement was observed in the cognitive domain. Speech/language developmental concern was an important red-flag indicator of cognitive and emotional/behavioral developmental delays. The presence of intellectual disability, autism spectrum disorder, and attention deficit hyperactivity disorder was high in this study. When having caregivers' concerns about speech/language and emotional/behavioral development, the odds of children with autism spectrum disorder was 2.37 and 2.17 times greater than those without autism spectrum disorder, respectively. The presence of attention deficit hyperactivity disorder was significantly associated with concerns about cognitive and emotional/behavioral developmental delays. Child's age and mothers' level of education were significant indicators for detecting the child's developmental problems. Conclusion It is recommended that assessing the cognitive developmental status is essential for all children in the identification process. Practitioners should not overlook caregivers' concern about speech/language and emotional/behavioral development. Transdisciplinary practitioners provide educational guidance to caregivers, especially in the domains of cognitive, speech/language, and emotional/behavioral development.